2008
DOI: 10.1186/1742-4690-5-68
|View full text |Cite
|
Sign up to set email alerts
|

HLA-C increases HIV-1 infectivity and is associated with gp120

Abstract: Virionic HLA-C molecules associate to Env and increase the infectivity of both R5 and X4 viruses. Genetic polymorphisms associated to variations in HLA-C expression levels may therefore influence the individual viral set point not only by means of a regulation of the virus-specific immune response but also via a direct effect on the virus replicative capacity. These findings have implications for the understanding of the HIV-1 entry mechanism and of the role of Env conformational modifications induced by virio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…Several evidences of the interaction between Env and HLA-C indicate that the presence of HLA-C is necessary to facilitate HIV-1 infection. The two molecules have been found associated and in the absence of HLA-C both fusion efficiency and virus infectivity are reduced345. In this work, a significant up-regulation of surface-HLA-C free chains, reactive to the L31 antibody18 was observed in HIV-1 chronically infected cells (ACH-2) following virus reactivation by TNF-α stimulation.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Several evidences of the interaction between Env and HLA-C indicate that the presence of HLA-C is necessary to facilitate HIV-1 infection. The two molecules have been found associated and in the absence of HLA-C both fusion efficiency and virus infectivity are reduced345. In this work, a significant up-regulation of surface-HLA-C free chains, reactive to the L31 antibody18 was observed in HIV-1 chronically infected cells (ACH-2) following virus reactivation by TNF-α stimulation.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies demonstrated the association between Env and HLA-C34. To analyse Env and HLA-C interaction, the Bimolecular Fluorescence Complementation (BiFC) assay was exploited.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations